A four-organ-chip for interconnected long-term co-culture of human intestine, liver, skin and kidney equivalents. Issue 12 (21st June 2015) - Maschmeyer, Ilka; Lorenz, Alexandra K.; Schimek, Katharina; Hasenberg, Tobias; Ramme, Anja P.; Hübner, Juliane; Lindner, Marcus; Drewell, Christopher; Bauer, Sophie; Thomas, Alexander; Sambo, Naomia Sisoli; Sonntag, Frank; et al.
<x xml:space="preserve">Abstract</x> We established a microfluidic four-organ-chip for interconnected long-term co-culture of human intestine (1), liver (2), skin (3) and kidney (4) equivalents.